2010
DOI: 10.1111/j.1549-8719.2010.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Reactivity of Optic Nerve Head and Retinal Blood Vessels in Glaucoma - A Review

Abstract: Glaucoma is characterized by loss of retinal nerve fibers, structural changes to the optic nerve, and an associated change in visual function. The major risk factor for glaucoma is an increase in intraocular pressure (IOP). However, it has been demonstrated that a subset of glaucoma patients exhibit optic neuropathy despite a normal range of IOP. It has been proposed that primary open angle glaucoma could be associated with structural abnormalities and/or functional dysregulation of the vasculature supplying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 167 publications
(270 reference statements)
0
70
0
1
Order By: Relevance
“…In fact, previous studies demonstrated that patients with glaucoma, in contrast to the control subjects, have an abnormal hyperactivity of ET-1 in response to vasospastic stimuli such as cold. 58 It has been postulated that an imbalance between vasoconstrictor substances such as 59,60 It was reported that patients with glaucoma who have vasospasm have a higher susceptibility to glaucomatous damage, which could be a consequence of a decreased dilation of blood vessels that properly autoregulate blood flow. 55 If our speculation is correct, BCACs induce normalization of ET-1, and its receptor balance may be beneficial for ocular blood circulation, since an increased ET-1 reactivity could lead to decreased ocular blood flow as indicated above.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous studies demonstrated that patients with glaucoma, in contrast to the control subjects, have an abnormal hyperactivity of ET-1 in response to vasospastic stimuli such as cold. 58 It has been postulated that an imbalance between vasoconstrictor substances such as 59,60 It was reported that patients with glaucoma who have vasospasm have a higher susceptibility to glaucomatous damage, which could be a consequence of a decreased dilation of blood vessels that properly autoregulate blood flow. 55 If our speculation is correct, BCACs induce normalization of ET-1, and its receptor balance may be beneficial for ocular blood circulation, since an increased ET-1 reactivity could lead to decreased ocular blood flow as indicated above.…”
Section: Discussionmentioning
confidence: 99%
“…38 The overall null association may have been due to the inclusion of SNPs from gene-regulating factors that may affect blood pressure or regulate vascular tone systemically but are not relevant for blood flow regulation, especially to the optic nerve head (ONH). For example, hormones such as epinephrine, vasopressin, and natriuretic peptides [40][41][42] or neurogenic factors 43 are unlikely to affect the regulation of blood flow to the retina and the ONH (e.g., blood vessels in the retina and the ONH are not innervated), 40 whereas intrinsic factors such as vascular endothelial vasoactive agents have an important role in influencing blood flow autoregulation and vascular tone in the ONH. 3,44,45 Of these agents, NO, generated constitutively by eNOS, has a key role in maintaining the basal vasodilator tone in ocular arteries.…”
Section: Discussionmentioning
confidence: 99%
“…3,44,45 Of these agents, NO, generated constitutively by eNOS, has a key role in maintaining the basal vasodilator tone in ocular arteries. 40,[46][47][48][49][50][51][52] The major contribution of NO to vascular tone in human ocular vasculature is demonstrated by the observation that systemic administration of an NOS inhibitor reduced blood flow in the ONH [53][54][55] and by the involvement of NO in the POAG-related vascular conditions, such as hypertension, hypotension, and vasospasms. 56 Evidence of abnormal NO production in glaucoma is also provided by genetic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested a larger diurnal fluctuation of parameters for ocular blood flow including ONH blood flow in patients with POAG or NTG (Claridge & Smith, 1994;Chung et al, 1999;Okuno T et al, 2004;Pemp et al, 2009). There has also been some evidence that endothelin (ET)-1 and nitric oxide may play roles in the dysregulation of ocular blood flow in glaucoma (Yorio et al, 2002;Flammer et al, 2007;Polak et al, 2007;Nicolela, 2008;Venkataraman et al, 2010). There have been some studies on the effects of anti-glaucoma medication on ONH blood flow.…”
Section: Introductionmentioning
confidence: 99%